Effects of the iron chelator deferiprone and the T-type calcium channel blocker efonidipine on cardiac function and Ca2+regulation in iron-overloaded thalassemic mice - Juthamas Khamseekaew (2018)
© 2018 Elsevier Ltd Although disturbance of cardiac Ca 2+ regulation is involved in the pathophysiology of iron-overload cardiomyopathy, the obvious mechanisms involved in the dysregulation of iron-induced cardiac Ca 2+ are unclear. Moreover, the roles of the iron chelator deferiprone and the T-type calcium channel blocker efonidipine on cardiac intracellular Ca 2+ transients and Ca 2+ regulatory proteins in thalassemic mice are still unknown. We tested the hypothesis that treatment with either deferiprone or efonidipine attenuated cardiac Ca 2+ dysregulation and led to improved left ventricular (LV) function in iron-overloaded thalassemic mice. Wild-type (WT) mice and β-thalassemic (HT) mice were fed with either a normal diet (ND) or a high iron-diet (FE) for 90 days. Then, the FE-fed mice were treated with either deferiprone (75 mg/kg/day) or efonidipine (4 mg/kg/day) for 30 days. ND-fed HT mice had an increase in T-type calcium channels (TTCC) and an increased level of sarcoplasmic reticulum Ca 2+ -ATPase (SERCA), compared with ND-fed WT mice. Chronic iron feeding led to an increase in TTCC and expression of SERCA proteins in FE-fed WT mice. Moreover, chronic iron overload led to increased plasma non-transferrin bound iron (NTBI) and cardiac iron deposition, impaired cardiac intracellular Ca 2+ transients including decreased intracellular Ca 2+ transient amplitude, rising rate and decay rate, as well as impaired LV function as indicated by a decreased %LV ejection fraction (%LVEF) in both WT and HT mice. Our findings showed that treatment with either deferiprone (DFP) or efonidipine (EFO) showed similar benefits in reducing plasma NTBI and cardiac iron deposition, and improving %LVEF from 84.3 (WT) to 89.3 (DFP) and 89.2 (EFO) treatment; and from 84.2 (HT) to 88.8 (DFP) and 89.5 (EFO) treatment, however there was no improvement in the regulation of cardiac Ca 2+ in iron-overloaded thalassemic mice. These findings provide the understanding of the effects of these drugs on the iron-overloaded heart in thalassemic mice and suggest that an alternative intervention that could improve calcium regulation under this condition is needed to improve the therapeutic outcome. Moreover, whether the benefits of the TTCC blocker is via its inhibition of the TTCC alone or together with its ability to chelate iron are stil l unclear and need further investigation.